2016
DOI: 10.1080/0284186x.2016.1221532
|View full text |Cite
|
Sign up to set email alerts
|

Considerable pancreatic tumor motion during breath-holding

Abstract: Background: Breath-holding (BH) is often used to reduce abdominal organ motion during radiotherapy. However, for inhale BH, abdominal tumor motion during BH has not yet been investigated. The aim of this study was to quantify tumor motion during inhale BH and tumor position variations between consecutive inhale BHs in pancreatic cancer patients. Material and methods: Twelve patients with intratumoral fiducials were included and asked to perform three consecutive 30-second inhale BHs on each of three measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…Earlier, we performed a patient study in which we determined the tumor motion during 30-second inhalation breath-holds with a lung volume of ~75% of the inspiratory capacity (lung volumes were determined using a spirometer) [13,14]. When comparing our current data to the patient data from that study, we see that the observed tumor motion magnitude in the IS direction during 30-second inhalation breath-holds in patients (mean: 4.7 mm; SD: 3.0 mm) was similar to the motion of the pancreatic head in the IS direction during the first 30 s of BH 70% in this study (mean: 4.8 mm; SD: 2.3 mm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, we performed a patient study in which we determined the tumor motion during 30-second inhalation breath-holds with a lung volume of ~75% of the inspiratory capacity (lung volumes were determined using a spirometer) [13,14]. When comparing our current data to the patient data from that study, we see that the observed tumor motion magnitude in the IS direction during 30-second inhalation breath-holds in patients (mean: 4.7 mm; SD: 3.0 mm) was similar to the motion of the pancreatic head in the IS direction during the first 30 s of BH 70% in this study (mean: 4.8 mm; SD: 2.3 mm).…”
Section: Discussionmentioning
confidence: 99%
“…The position variation of the tumor between multiple consecutive breath-holds, both inhalation and exhalation, has already been thoroughly determined for abdominal tumors [6,7,9,10,13,14]; mean variations of 1.2 and 2.3 mm were reported in the inferior-superior (IS) direction for inhalation and exhalation breath-holds, respectively [6,7]. The interfractional tumor position variation is similar for inhalation and exhalation breath-holds [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary drawback to respiratory gating is the lengthening of treatment times, although these can be accounted for by using high dose-rate, flattening-filter free beams. Another common technique requires that the patient hold their breath during treatment; however, this has been shown to have poor accuracy for pancreatic tumors [12]. Other methods attempt to track the tumor directly without the use of an external surrogate [13,14].…”
mentioning
confidence: 99%
“…Of these techniques, BH is one of the most commonly used owing to its versatility (2). Some researchers reported that BH was clinically useful in cases with disease sites such as the lung, breast, liver, and pancreas (6)(7)(8)(9)(10)(11). At our institution, VMAT has been used clinically under BH conditions at the end-exhalation (EE) phase for pancreatic cancer (9,12).…”
mentioning
confidence: 99%